Multicultural Little Italy: A Literary Comparison of Canadian and US Urban Enclaves - Sañudo, Eva Pelayo (Italian Canadiana, 2020)
Drawing on Paul Moses’ An Unlikely Union: The Love-Hate Story of New York’s Irish and Italians (2015), this article explores the history and literary reflection of multicultural cities. Particularly, Louisa Ermelino’s novel The Sisters Mallone (2002) challenges accepted views of certain urban enclaves as ghettos. This assumption obscures cross-cultural relations and renders superficial the term multicultural as only a mosaic of discrete cultures living together. In this respect, a comparison to official multiculturalism in Canada discusses the complex nature of identity and belonging. A unique case study is Quebec, as is reflected in the position of the trilingual writer and the affiliation to world literature. This article is divided into two parts. Firstly, it analyzes a literary text that looks at US ethnic relations beyond conflict and segregation. The second part, using Italian/Canadian literary history, reflects on Canada as a multicultural country characterized by cultural diversity yet where cultural difference entails unequal power relationships such as regarding migrants and migrant literature.